2018
DOI: 10.1037/drm0000090
|View full text |Cite
|
Sign up to set email alerts
|

Lucid nightmares: A survey of their frequency, features, and factors in lucid dreamers.

Abstract: This article reports the first systematic study on lucid nightmares-terrifying lucid dreams with a lack of dream control. An online survey was completed by 634 participants, of whom 574 had had previous lucid dream experience. According to the reports of lucid dreamers, less than half of them had experienced a lucid nightmare, and only 1% of them could be considered as suffering from lucid nightmares-experiencing them once a week or more frequently. Lucid nightmares appear to be as distressing as ordinary nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 40 publications
5
22
1
1
Order By: Relevance
“…Lucid nightmares may be even more terrifying than common nightmares (Halliday, 1988); however, Stumbrys (2018) found that the levels of nightmare vs. lucid nightmare distress do not differ. Sparrow (1991), signifying dreamer’s harrowing experiences with LD, warned about the wholesale advertising of LD, since lucid nightmares frequency is associated not only to nightmare frequency, but also to LD frequency (Stumbrys, 2018). This makes patients with nightmares very vulnerable to lucid nightmares in a LDT.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Lucid nightmares may be even more terrifying than common nightmares (Halliday, 1988); however, Stumbrys (2018) found that the levels of nightmare vs. lucid nightmare distress do not differ. Sparrow (1991), signifying dreamer’s harrowing experiences with LD, warned about the wholesale advertising of LD, since lucid nightmares frequency is associated not only to nightmare frequency, but also to LD frequency (Stumbrys, 2018). This makes patients with nightmares very vulnerable to lucid nightmares in a LDT.…”
Section: Discussionmentioning
confidence: 97%
“…Halliday (1988) and Zadra (1990) reported case studies in which lucidity was achieved, but without control, and it actually worsened the nightmare. Lucid nightmares are LD with a scary and unpleasant content, in which dreamers have no control over the situation, thus they just “witness” the unfolding of the dream, being unable to deliberately wake up (Hurd, 2009; Schredl and Göritz, 2018; Stumbrys, 2018). Lucid nightmares may be even more terrifying than common nightmares (Halliday, 1988); however, Stumbrys (2018) found that the levels of nightmare vs. lucid nightmare distress do not differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, because nightmares often involve diminished agency (i.e., helplessness, lack of control; e.g., McNamara et al., 2015), it is possible that lucid nightmares are even more difficult to control than regular lucid dreams. While comparative data are lacking, Stumbrys (2018) reports that a lack of dream control in present in about one third of lucid nightmares. In another study (Schredl & Goritz, 2018), individuals from the general population reported their most recent nightmare, which produced a subsample of lucid nightmares ( n = 39).…”
mentioning
confidence: 99%
“…Furthermore, although most nightmares feature themes of aggression, interpersonal conflicts, or being chased (suggesting the presence of a threatening dream character; McNamara et al., 2015; Robert & Zadra, 2014), this is not always the case. According to a recent study (Stumbrys, 2018), only 28% of lucid nightmares feature a violent autonomous dream character. If a lucid nightmare does not feature a threatening dream character, the aforementioned strategies (i.e., fighting and dialoguing) cannot be used.…”
mentioning
confidence: 99%